Perencanaan Enterprise Architecture pada Perusahaan Manufaktur Plastik PT. X dengan Metode Enterprise Architecture Planning - Wilson Surya Nyoto; Adi Wibowo; Lily Puspa Dewi (Jurnal Infra, 2016)
Plastic manufacturing company PT. X is a company engaged in the production of plastic goods, products such as dvd case or cutlery. Almost all business processes performed by the company are using manual data collection and few are integrated. The company uses Microsoft Office and Accurate but Microsoft Office is not well integrated and part Accurate program does not include all the needs of business processes in the company today. Therefore, an analysis will be formed, with it also a design of enterprise architecture using enterprise architecture planning method for plastic manufacturing company PT. X. The first to be done is to analyze the business model of the company and the company strategies. Then observation of existing information technology in today and see the need in the future for the company. After these things done, one can begin to make the design data architecture, application and technology.